The Maghrib in the Mashriq Knowledge, Travel and Identity - Fierro, Maribel; Penelas, Mayte (Studies in the History and Culture of the Middle East, 2021)
This book is about the impact of knowledge produced in the Islamic West on the Mashriq. Topics include the emergence and construction of the concept 'Maghrib', the role of travel in the transmission, reception and integration of locally produced knowledge, and the ways in which Maghribis in the Mashriq manifested their identity. The studies are of interest for understanding the complex dynamics between local and global intellectual contexts.